Comparison of discrete, discrete-sectional, modal and moment models for aerosol dynamics simulations. Issue 7 (2nd July 2020) - Zhang, Huang; Sharma, Girish; Dhawan, Sukrant; Dhanraj, David; Li, Zhichao; Biswas, Pratim
Abstract: An open source software (Aerosol and Air Quality Research Lab-Aerosol Dynamics Model, AAQRL-ADM) used for aerosol dynamics simulations is developed by including four models: discrete, discrete-sectional, method of moments, and modal. First, the mathematical description of these models as well as the effects of aerosol dynamics available in the software are reviewed, and a modal model is developed to use multiple modes to represent particle size spectrum. Second, the design of a working principle and user graphical interface (GUI) of AAQRL-ADM is described. Third, the models in AAQRL-ADM are validated by investigating the evolution of particle size distribution (PSD) in considering the effects of coagulation, condensation, and nucleation. Next, the trade-off between simulation accuracy and numerical efficiency is discussed for all of the four models, and a guide to choosing the appropriate aerosol dynamic model in practical simulation is presented. Finally, discrete-sectional, moment, and modal models are used to investigate the particle size distribution in a furnace aerosol reactor along a streamline, coupled with the velocity and temperature profiles. AAQRL-ADM is provided free of charge for the use of public researchers. Copyright © 2020 American Association for Aerosol Research